IMPLEMENTASI PERAN KEPOLISIAN DAN HAMBATAN-HAMBATANNYA DALAM MENGUNGKAPKAN KASUS PEMBUNUHAN BERENCANA DI WILAYAH KEPOLISIAN RESOR SABU-RAIJUA - Banga, Ar; Leo, Rudepel Petrus; Amalo, Heryanto (Petitum Law Journal, 2024)
Premeditated murder in the Criminal Code (KUHP) is regulated in article 340 of the Criminal Code, which states: "Anyone who deliberately and with premeditation takes the life of another person, is threatened with premeditation, with the death penalty or imprisonment for life or for a certain period of time a maximum of 20 years. This research aims to find out the role of the police in disclosing cases of premeditated murder in the Sabu-Raijua resort area, and what obstacles they experience in disclosing these cases, as well as the factors that cause the crime of premeditated murder and arriving at solutions faced by investigators in the process. investigation. This research uses empirical juridical methods, namely methods that are studied through field research approaching existing facts and then using relevant laws and regulations as a basis for reviewing analyzing legal research as a reference for problem solving. Looking for the factors causing the occurrence and handling, obtained from primary and secondary data from interviews with the police (criminal investigators), village heads, community leaders and victims' families. As well as with literature studies and qualitative descriptive data analysis. The results of this research show that the role of the police in uncovering criminal cases of premeditated murder is very important, because the role of the police in criminal justice is at the forefront. Namely by carrying out the duties of an investigator related to arrest, detention, searches, confiscation of evidence, examination of documents and witnesses, suspects and assistance from experts. In doing this, the police are tasked with finding out the real truth. Apart from that, this research aims to find out what obstacles are faced and what solutions there are to get the truth about the causes of premeditated murder crimes in the Sabu-Raijua Resort area.